The Masticatory Contractile Load Induced Expression and Activation of Akt1/PKBα in Muscle Fibers at the Myotendinous Junction within Muscle-Tendon-Bone Unit. (18th April 2010) - Korkmaz, Yüksel; Klinz, Franz J.; Moghbeli, Mehrnoush; Addicks, Klaus; Raab, Wolfgang H.-M.; Bloch, Wilhelm
Abstract : The cell specific detection of enzyme activation in response to the physiological contractile load within muscle-tendon-bone unit is essential for understanding of the mechanical forces transmission from muscle cells via tendon to the bone. The hypothesis that the physiological mechanical loading regulates activation of Akt1/PKBα at Thr308 and at Ser473 in muscle fibers within muscle-tendon-bone unit was tested using quantitative immunohistochemistry, confocal double fluorescence analysis, and immunoblot analysis. In comparison to the staining intensities in peripheral regions of the muscle fibers, Akt1/PKBα was detected with a higher staining intensity in muscle fibers at the myotendinous junction (MTJ) areas. In muscle fibers at the MTJ areas, Akt1/PKBα is dually phosphorylated at Thr308 and Ser473. The immunohistochemical results were confirmed by immunoblot analysis. We conclude that contractile load generated by masticatory muscles induces local domain-dependent expression of Akt1/PKBα as well as activation by dually phosphorylation at Thr308 and Ser473 in muscle fibers at the MTJ areas within muscle-tendon-bone unit.